Fostering Intercultural Competence of Students during Translation Classes at the John Paul II Catholic University of Lublin - Waterlot, Muriel (Werkwinkel, 2016)
Intercultural communication has become a scientific discipline which aims at improving communication during intercultural contacts by means of fostering the intercultural awareness and competence of the interlocutors involved within the intercultural communication process. In view of the intensifying European and international contacts the interest for this competency has grown during the last decades. This can among others be observed within foreign language teaching, but also in the training of translators at university level where new didactical approaches and teaching methods are being developed in order to improve the intercultural of future translators. This article presents a preliminary collaboration between the John Paul II Catholic University of Lublin and non-profit organization of translators, as well as the theoretical and practical backgrounds of a project which that they envisage to realize in future in order to transform its participants into intercultural competent translators.